2022
DOI: 10.2147/jir.s344861
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Significant Modules and Targets of Xian-Lian-Jie-Du Decoction Based on the Analysis of Transcriptomics, Proteomics and Single-Cell Transcriptomics in Colorectal Tumor

Abstract: Purpose Colorectal cancer (CRC) remains the third most common tumor worldwide. Ulcerative colitis (UC) could cause chronic inflammation and ulcers in the colon and rectum. UC is a risk factor for a high incidence of CRC, and the incidence of UC-associated CRC (UC-CRC) is still increasing. Chinese medicine prescription, Xian-Lian-Jie-Du decoction (XLJDD), has been proven its efficacy in some UC-CRC patients. However, the mechanism of XLJDD in treating UC-CRC remains unknown. This study aimed to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Therefore, a lower expression of CCDC85C was a predictor of poorer survival in CRC patients [37]. Many studies confirmed differential expression of circRNAs between normal colon and CRC cell lines [38,39]. Analysis of a ceRNA sub-network showed that circRNA-SHPRH and circ-CEP128 regulated the expression of hsa-miR-331-3p and hsa-miR-145-5p, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, a lower expression of CCDC85C was a predictor of poorer survival in CRC patients [37]. Many studies confirmed differential expression of circRNAs between normal colon and CRC cell lines [38,39]. Analysis of a ceRNA sub-network showed that circRNA-SHPRH and circ-CEP128 regulated the expression of hsa-miR-331-3p and hsa-miR-145-5p, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, membrane proteomic analysis was conducted on the intestinal mucosa from an AOM/DSS-induced mouse model of colon cancer. Although previous proteomic studies utilizing the AOM/DSS mouse model have explored proteins related to colon cancer [32][33][34][35][36][37], membrane proteomic studies are limited, hindering the investigation of lower abundance and insoluble membrane proteins. In this study, membrane proteomic analysis revealed the regulation of metabolic pathways in tumor tissues compared with that in the adjacent normal colon tissues.…”
Section: Discussionmentioning
confidence: 99%
“…XLJDOD is an empirical prescription used as an adjuvant treatment of colorectal cancer for more than 10 years in China. Basic biological research confirms that XLJDOD effectively inhibits tumor cell proliferation and migration, modulates tumor microenvironment, regulates the function of immune cells [ 54 ā€“ 56 ].…”
Section: Discussionmentioning
confidence: 99%